2011
DOI: 10.1007/s12263-011-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance determinants in the interplay between food and gut microbiota

Abstract: A complex and heterogeneous microflora performs sugar and lactic acid fermentations in food products. Depending on the fermentable food matrix (dairy, meat, vegetable etc.) as well as on the species composition of the microbiota, specific combinations of molecules are produced that confer unique flavor, texture, and taste to each product. Bacterial populations within such “fermented food microbiota” are often of environmental origin, they persist alive in foods ready for consumption, eventually reaching the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 89 publications
3
71
0
2
Order By: Relevance
“…The detection of antibiotic resistant (AR) strains among LAB has resulted in their recognition as a reservoir of AR genes horizontally transmissible to pathogens through the food chain, which constitutes a problem [111,112]. Antibiotic multiresistant strains of lactobacilli and other LAB have been isolated from dry-fermented meat products [113][114][115][116][117][118][119][120].…”
Section: Assessment Of Antibioresistancementioning
confidence: 99%
“…The detection of antibiotic resistant (AR) strains among LAB has resulted in their recognition as a reservoir of AR genes horizontally transmissible to pathogens through the food chain, which constitutes a problem [111,112]. Antibiotic multiresistant strains of lactobacilli and other LAB have been isolated from dry-fermented meat products [113][114][115][116][117][118][119][120].…”
Section: Assessment Of Antibioresistancementioning
confidence: 99%
“…Moreover, the strains of L. plantarum MT.ZH293 and MT.ZH593 were also resistant to tetracycline (Table 2). Devirgiliis et al [2011] also reported on the resistance of lactobacilli from cheese to erythromycin, tetracycline and chloramphenicol.…”
Section: Surface Hydrophobicitymentioning
confidence: 99%
“…Heavy-metal and antibiotic resistance genes are often encoded together on the same plasmid, so a selective pressure exists to keep the plasmid in the intestinal tract (22).…”
Section: Microbial Mechanisms Of Actionmentioning
confidence: 99%